Multiple-aperture speckle method applied to local displacement measurements (2007)
The goal of this work is to analyze the measurement capability of the modified speckle photography technique that uses different multiple aperture pupils in a multiple exposure scheme. In particular, the rotation case is considered. A point-wise analysis procedure is utilized to obtain the fringes required to access to the local displacement measurements. The proposed arrangement allows simultaneous displaying in the Fourier plane several fringes system each one associated with different rotations. We experimentally verified that the local displacement measurements can be determined with a high precision and accuracy.